Roasting of the spices - Mumbai Archive Project Team (Jio Institute, 2024)
Once the spices are dried until crispy, each is roasted to a specific temperature, ranging from mild to high. The oils released during this roasting process enhance the aroma and flavour, giving it a more complex and robust taste.